A polyisoprenylated ketone from Calophyllum enervosum - Taher, Muhammad; Idris, Muhammad Sum; Ahmad, Farediah; Arbain, Dayar (Elsevier Ltd., 2005)
A polyisoprenylated ketone named enervosanone has been isolated from the stem bark of Calophyllum enervosum together with three known compounds, cambogin, osajaxanthone and epicatechin. Their structures were determined by spectroscopic analysis. The antimicrobial evaluations of the isolated compounds were also reported.